2003
DOI: 10.1167/iovs.03-0253
|View full text |Cite
|
Sign up to set email alerts
|

Expression ofPRPF31mRNA in Patients with Autosomal Dominant Retinitis Pigmentosa: A Molecular Clue for Incomplete Penetrance?

Abstract: Partial penetrance in RP11 could be due to the coinheritance of a PRPF31 gene defect and a low-expressed wild-type allele. This study revealed a potential avenue for future therapy in that it appears the moderate overexpression of wild-type PRPF31 may prevent clinical manifestation of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
103
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(110 citation statements)
references
References 18 publications
7
103
0
Order By: Relevance
“…Rivolta et al studied the effect of five mutations on the expression levels of the PRPF31 gene, and found that asymptomatic carriers had PRPF31 mRNA levels similar to normal control individuals [10]. A similar finding was also made in lymphoblasts from a large RP11 family with an 11-bp deletion in exon 11 [16]. Together, these results may provide an important clue to understanding of the molecular mechanism explaining the phenotypic variability among RP11 patients.…”
mentioning
confidence: 79%
“…Rivolta et al studied the effect of five mutations on the expression levels of the PRPF31 gene, and found that asymptomatic carriers had PRPF31 mRNA levels similar to normal control individuals [10]. A similar finding was also made in lymphoblasts from a large RP11 family with an 11-bp deletion in exon 11 [16]. Together, these results may provide an important clue to understanding of the molecular mechanism explaining the phenotypic variability among RP11 patients.…”
mentioning
confidence: 79%
“…The molecular mechanisms underlying this incomplete penetrance of Prp31 mutations in patients remain to be investigated. Possible explanations include differential expression of the wild type allele among different carriers or asymptomatic patients (Vithana et al, 2003) or the presence of a modifier gene (Rio Frio et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Many PRPF31 pathogenic alleles are null mutations, which have been previously shown to cause RP by haploinsufficiency, mainly through the NMD surveillance mechanism. 10,13,14 The variation in the levels of expression of the remaining wild-type allele directly correlates with incomplete penetrance in pedigrees. 11 Moreover, this expression variation has been shown to be a highly heritable character, depending on at least two transacting expression quantitative trait loci (eQTLs) (expression quantitative trait locus), which would therefore act as genetic modifiers.…”
Section: Discussionmentioning
confidence: 99%
“…Two of the adRP families had a large number of affected and nonaffected members available for analysis (families A6 and E4, Figure 1), whereas the size of the other two was much smaller (families A8 and A9, Figure 1), with merely 2-3 affected live members. Incomplete penetrance is relatively frequent in dominantly inherited disorders, such as adRP, 10,11 and thus, it was also taken into account while carrying out the co-segregation analysis. Also in our families there were some obligate carriers, who were non-penetrant but had affected progeny.…”
Section: Genotyping Of Autosomal Dominant Retinitis Pigmentosa Familiesmentioning
confidence: 99%